(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To assess immediate and late treatment outcomes of radiation therapy (RT) plus cryosurgery for the treatment of conjunctival melanoma (CM). Material and Methods: The study sample consisted of 88 patients who underwent RT plus cryosurgery for the treatment of CM at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” during 2004-2024. Of these CM patients, 45 (52.1%) were males (age range, 20 to 88 years; median, 54.1 years), and 43 (47.9%) were females (age range, 26 to 87 years; median, 56.6 years). Results: After RT plus cryosurgery, complete tumor resorption was seen in 77 patients (87.5%), and partial tumor resorption in 11 patients (12.5%). At 3 to 6 months, additional cryodestruction was performed in 8 patients (9.1%) with partial tumor resorption, which resulted in complete tumor resorption. Therefore, local control was attained in 85 patients (96.6%) after RT plus cryosurgery. Tumor recurrence was observed in 12.5% of patients, appeared as a nodule within the site of the primary tumor, and was successfully cured with cryodestruction. After RT plus cryosurgery, patients were followed up for 1 to 7 years (median, 5.1 years). Regional lymph node metastasis developed after treatment for CM in 8 patients (9.1%). Two patients developed distant metastasis. One of them developed metastasis in the lung five years post-treatment and another in the brain three years post-treatment, and tumor resorption was observed at the initial site of CM in both patients. Persistent tumor ingrowth in the orbit necessitated orbital exenteration in 3 patients (3.4%) with iatrogenic tumor. Conclusion: RT plus cryosurgery is an effective method of treatment for CM with an efficacy of treatment up to 96.6% and a recurrence rate of 12.5%. The method extends opportunities for organ-preserving treatment for CM and enables retreatment in case of tumor recurrence, with rather good functional and esthetic outcomes and improved patient’s quality of life.